STUDY UTILIZATION OF SEAWEED (Eucheuma sp.) AS AN ADSORBENT OF HEAVY METAL IONS Cr(VI).: Indonesia - -, Gusti Dwi Intan Lestari (Jurnal Sains Indonesia, 2024)
This study focuses on the use of seaweed (Eucheuma sp.) as a heavy metal ion adsorbent for Cr(VI). The type of acid, acid concentration, contact time, and seaweed's capacity as an adsorbent have all been examined in order to establish the best conditions for the adsorption of Cr(VI) ions. According to the findings, sulfuric acid (H2SO4) at a concentration of 1 M, 60 minutes of contact time variation, and 91.82 percent Cr(VI) adsorption were the ideal conditions for Cr(VI) adsorption. Additionally, several concentrations of Cr(VI) ion sample solution were exposed to the adsorbent, with the best results occurring at 25 ppm and 91,81% Cr(VI) adsorption. Natural dye wastewater with an initial Cr(VI) ion concentration of 1,3519 ppm to 0,1345 ppm and textile dye wastewater with an initial Cr(VI) ion concentration of 3,2317 ppm to 0,2908 ppm were both treated under ideal conditions. Natural dye wastewater has a Cr(VI) ion adsorption percentage of 90,05%, whereas textile dye wastewater has a 91,01% adsorption percentage.